Pattern of lumbar disc degeneration in young adults with low back pain on 3.0t magnetic resonance imaging machine - Saleem, Ramsha; Sara Khan; Atiq Ur Rehman Slehria; Hafsa Aquil; Aliya Halim (Journal of the Pakistan Medical Association, 2025)
Objectives: To determine the frequency and patterns of lumbar disc degeneration in young adults with low back pain. Method: The descriptive, cross-sectional study was conducted at the Armed Forces Institute of Radiology and Imaging, Rawalpindi, Pakistan, from August 16, 2023, to February 15, 2024, and comprised patients of either gender aged 18-35 years who presented with low back pain. The participants were subjected to examination using 3.0T magnetic resonance imaging machine. Lumbar disc degeneration was noted and its patterns were assessed. Lumbar disc degeneration was graded using Pfirmann grading. Data was analysed using SPSS 25. Results: Of the 146 patients with mean age 25.62.98 years, 103(70.5%) were males and 43(29.5%) were females. Lumbar disc degeneration was present in 85(58.2%) patients, and multilevel involvement was seen in 45(30.8%). The most common involvement was of L3-L4 12(8.2%), followed by L4-L5 11(7.5%). The most common lumbar disc degeneration grade was grade III 39(26.7%), followed by grade IV 25(17.1%). Conclusion: In more than half of the young adults with low back pain, lumbar disc degeneration was present because of either single or multiple level of vertebrae involvement. Key Words: Lumbar disc degeneration, Young adults, Low back pain.